Building Design Effect on Indoor Natural Ventilation of Tropical Houses - Abd Wahab, Izudinshah; Abd Aziz, Hazri; Abd Salam, Nur Nasuha (International Journal of Sustainable Construction Engineering and Technology, 2019)
Air movement is one of the important parameter to establish a good indoor thermal condition. Due to the public environmental concern, people are becoming more interested on turning to the natural sources in achieving the parameters. With a good design approach considering the matters, building is expected to be able to provide good indoor natural ventilation flow inside, hence keeping comfort to its habitable spaces. As being studied before, there are type of houses that contribute to its indoor natural ventilation. However, a proper design solution may still required in determining the design elements to be used. This research defined the significant elements as a proper specified attributes which were observed in case studies. Three categories of tropical houses were studied under the category of vernacular house, contemporary house with vernacular element and contemporary house. Spaces of the houses that indicate good indoor natural ventilation performance were observed on the presence of the specified attributes. Based on the analysis, wind catcher element was found to be the most significant attribute to contribute the maximum to indoor natural ventilation. Wide opening was also found to be significant especially with those with louvers. It is also interesting to find how indoor layout design also significantly giving impact on the performance. Therefore, besides concerning on how to extract the outdoor air flow into building, it is also important to manage the indoor air flow effectively to benefit the occupants.